INDUSTRY PARTNERSHIPS LEARNING MODELS FOR SURVEYING AND MAPPING OF VOCATIONAL HIGH SCHOOLS - Sunar Rochmadi (Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
This study aims to identify a learning involving the world of work, to formulate the learning model, and to evaluate the learning model. This study used a qualitative approach for design and development research, consisting of the development and validation steps. The study concludes as follows. (1) the learning through partnerships having been conducted in all vocational high schools were industrial practice and vocational practice examination. (2) the constraints of learning through partnerships were mainly the far distance and the industry schedules that did not always match with the school’s. (3) the model development could be done by improving the learning quality by industrial practices in the private companies and with adding the learning model by industry visits, guest teaching, and up-to-date technology training. (4) the implementation of the developed model showed the feasibility and the effectiveness to prepare the students with the competencies required by the world of work. (5) the learning models through partnerships that could be practiced were guest teaching, orientation for industrial practice, industrial practices, students’ industry visits, up-to-date technology training, and vocational practice examination.